Evaluation of Shifts in the Potential Future Distributions of Carcharhinid Sharks Under Different Climate Change Scenarios - Diaz-Carballido, Pedro Luis; Mendoza-González, Gabriela; Yañez-Arenas, Carlos Alberto; Chiappa-Carrara, Xavier (Frontiers in Marine Science, 2022)
Climate change is currently considered one of the main phenomena affecting marine species through expansion or contraction of their distribution. Being ectothermic organisms, sharks of the family Carcharhinidae could be highly susceptible to the effects of climate change. These sharks are of great ecological importance, which is reflected in their role in the integrity of coastal and oceanic ecosystems as top predators that act to maintain the stability of the food chain, as well as providing economic value through fishing, consumption, and ecotourism. Currently, their populations are threatened by fishing pressure and anthropogenic activities, including meeting the demand for shark fins. Despite the ecological and economical importance of carcharhinid sharks, knowledge regarding how they are impacted by climate change remains scarce. Ecological niche modeling is a tool that allows analysis of future potential distributions under different climate change scenarios and could contribute to future planning activities and improved conservation outcomes for sharks. We generated models in Maxent in order to predict the potential geographic distribution of 25 carcharhinid sharks that inhabit Mexican waters, projecting this onto future climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) to calculate the potential losses and gains in their distribution areas by the year 2050. The greatest shifts in suitable areas were observed for the sharks Triaenodon obesus (gained area) and Carcharhinus porosus (lost area). Overall, under all four RCP future scenarios, six species presented gains in suitable area and 19 species presented losses. The greatest loss of suitable area for carcharhinid sharks was found with RCP8.5; however, under this high-emissions global warming scenario, seven species actually showed an increase in distribution area. Our results therefore indicate that climate change could reduce suitable areas for most of the species by 2050. Assessment of the distribution of shark species under climate change is urgently required in order to prioritize conservation efforts toward the most vulnerable species and to ensure the natural function of marine ecosystems, thus maintaining the important ecosystem services they provide to human society.